Effects of Loyalty Programs on Value Perception, Program Loyalty, and Brand Loyalty - Yi, Youjae; Jeon, Hoseong (Journal of the Academy of Marketing Science, 2003)
The authors investigate how reward schemes of a loyalty program influence perceived value of the program and how value perception of the loyalty program affects customer loyalty. The results show that involvement moderates the effects of loyalty programs on customer loyalty. In high-involvement situations, direct rewards are preferable to indirect rewards. In low-involvement situations, immediate rewards are more effective in building a program's value than delayed rewards. Under high-involvement conditions, value perception of the loyalty program influences brand loyalty both directly and indirectly through program loyalty. Under low-involvement conditions, there is no direct effect of value perception on brand loyalty. [PUBLICATION ABSTRACT]